64 An evaluation of the efficacy of precision teaching for improving clinical skills among medical students. (17th November 2016) - Lydon, S; Burns, N; Healy, O; O'Connor, P; Reid-McDermott, B; Byrne, D
Abstract : Introduction: The insufficiency of traditional approaches to medical education is well recognised. Simulation technologies allow medical students to better prepare for the clinical environment and contribute to improved patient safety. However, the instructional design utilised with simulation is of much importance. The current study evaluated a novel approach to simulation education by employing precision teaching- a behavioural teaching strategy widely used in other areas of education- to improve the clinical skills of medical students. Method: This study included three groups. The intervention group consisted of 11 fourth year medical students. The first control group included 11 other fourth year medical students. The second control group consisted of 11 non-consultant hospital doctors (NCHDs). Control group participants' did not receive any training and were asked to perform venepuncture only once. The intervention group students received training in venepuncture with simulation in combination with precision teaching and peer-tutoring. Eight weeks following the cessation of training, the intervention group participants' performance was assessed. Participants' performance of another needle-based clinical skill (cannulation) was also assessed, along with their performance in the presence of distraction, and their performance of venepuncture with patients in the clinical environment. Results: Participants in the intervention group outperformed their fourth year peers and the NCHDs. Participants' skills had not decayed at the two month follow-up, nor did they deteriorate in the presence of distraction. Participants' learning generalised to the clinical environment. Further, although not directly trained, their ability to perform cannulation was greater than that of controls. Discussion: The use of precision teaching in combination with simulation to teach clinical skills may be a promising strategy. Precision teaching produces behavioural fluency which ensures that behaviour persists over time, does not deteriorate during distraction, and generalises to other skills or settings, including with real patients outside of the simulation laboratory.